Examination of bidirectional relationships between fear of negative evaluation and weight/shape concerns over 3 years: A longitudinal cohort study of Australian adolescents. Issue 3 (6th January 2023) - Trompeter, Nora; Austen, Emma; Bussey, Kay; Reilly, Erin E.; Cunningham, Mitchell L.; Mond, Jonathan; Lonergan, Alexandra; Tame, Jack; Mitchison, Deborah
Abstract: Objective: Adolescents commonly experience both fear of negative evaluation and weight/shape concerns. However, evidence concerning the prospective associations between these constructs during adolescence is limited. The current study examined the bidirectional relationships between fear of negative evaluation and weight/shape concerns over a 3‐year period in adolescents. Method: Australian high school students ( n  = 2073; 55% girls) completed self‐report measures at three timepoints, each 1 year apart. Results: Findings showed a bidirectional relationship, whereby increases in fear of negative evaluation predicted exacerbated weight/shape concerns, and vice versa. Results point towards a vicious maintenance cycle between fear of negative evaluation and weight/shape concerns. Discussion: Findings from the current study highlight the importance of considering both fear of negative evaluation and weight/shape concerns in the development of health promotion and prevention programs designed to reduce the occurrence and adverse effects of body dissatisfaction or improve general mental health. Public Significance: Many adolescents experience some level of fear of negative evaluation (i.e., worry about being judged by others) and worry about their weight and/or shape. This study examined the prospective relationship between both constructs. Findings showed a bidirectional relationship, whereby higher fear of negative evaluation predicted increased weight/shape concerns, and vice versa. Programs designed to reduce body dissatisfaction might be improved by targeting both fear of negative evaluation and weight/shape concerns.